Lead and cadmium clean removal from wastewater by sustainable biochar derived from poplar saw dust. (10th September 2021) - Cheng, Song; Liu, Yongzhi; Xing, Baolin; Qin, Xiaojing; Zhang, Chuangxiang; Xia, Hongying
Abstract: Biochar is produced at 400–800 °C by pyrolysis of poplar saw dust, which is used as the sustainable adsorbent to investigate the adsorption performance of Pb 2+ /Cd 2+ from wastewater. The adsorption kinetics and isotherms of Pb 2+ /Cd 2+ on biochar were determined. The maximum adsorption amount of Pb 2+ is 62.68 mg/g, while that of Cd 2+ is 49.32 mg/g at pH of 5 based on Langmuir equation. The Cd 2+ adsorption was seriously inhibited, while the uptake of Pb(II) was not significantly affected in the multimetal system. The adsorption performance of Pb 2+ /Cd 2+ was also investigated in different water systems. Mineral precipitation with Pb 2+ is predominant mechanism for Pb 2+ removal with the contribution proportion of 51.76%. Coordination with π electrons is the primary mechanism for Cd 2+ adsorption, at 59.36% of the total adsorption capacity. Our findings provide a successful example of poplar saw dust converting into the sustainable adsorbent for Pb 2+ /Cd 2+ removal from wastewater to implement the concept of "clean production", which is worthy of further study. Graphical abstract: Cadmium and lead adsorption removal from wastewater by biochar derived from poplar saw dust. Image 1 Highlights: Poplar saw dust biochar shows high Pb 2+ and Cd 2+ adsorption capacity. Pb 2+ has a greater affinity for studied biochar than Cd 2+ . Precipitation with mineral dominates Pb 2+ adsorption mechanism on biochar. Coordination with π electrons is the primary mechanism for Cd 2+ adsorption on biochar.